The robot the life story of a technology - Nocks, Lisa (The Johns Hopkins University Press, 2008)
This volume includes a timeline of important events, a glossary of terms, descriptions and statistics of robot labs and companies around the world, and a helpful bibliography of primary and secondary sources for further research